2016
DOI: 10.5194/amt-9-2303-2016
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a channel for XCO observations to a portable FTIR spectrometer for greenhouse gas measurements

Abstract: Abstract. The portable FTIR (Fourier transform infrared) spectrometer EM27/SUN, dedicated to the precise and accurate observation of column-averaged abundances of methane and carbon dioxide, has been equipped with a second detector channel, which allows the detection of additional species, especially carbon monoxide. This allows an improved characterisation of observed carbon dioxide enhancements and makes the extended spectrometer especially suitable as a validation tool of ESA's Sentinel 5 Precursor mission,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 26 publications
3
82
1
Order By: Relevance
“…The EM27/SUN spectrometer is described in more detail in Gisi et al (2012), Frey et al (2015), and Hase et al (2016). CH 4 is retrieved from EM27/SUN solar spectra (5,000-11,000 cm −1 ) using the spectral region at 5,897-6,145 cm −1 and O 2 at 7,765-8,005 cm −1 (Frey et al, 2015); the PROFFIT code is used for the retrievals (Hase et al, 2004).…”
Section: Retrievalsmentioning
confidence: 99%
“…The EM27/SUN spectrometer is described in more detail in Gisi et al (2012), Frey et al (2015), and Hase et al (2016). CH 4 is retrieved from EM27/SUN solar spectra (5,000-11,000 cm −1 ) using the spectral region at 5,897-6,145 cm −1 and O 2 at 7,765-8,005 cm −1 (Frey et al, 2015); the PROFFIT code is used for the retrievals (Hase et al, 2004).…”
Section: Retrievalsmentioning
confidence: 99%
“…Hase et al (2016) have also reported on X CO measurements using an EM27/SUN modified to include a second InGaAs detector with optical filters. Column CO measurements are desirable because CO is a tracer of combustion.…”
Section: Co and X N 2 Omentioning
confidence: 99%
“…EGI provides a simple way to turn on and off saving of ancillary retrieval files (i.e., spectral fits and averaging kernels). EGI can run for instruments employing one or two detectors, such as the type described by Hase et al (2016). Like the GGG software suite, EGI also includes benchmark spectra acquired under different conditions to run simple tests on.…”
Section: Em27/sun Ggg and Interferogram Processing Suite (Egi)mentioning
confidence: 99%
“…Quality filtering, based on the unmodulated (DC) part of the recorded interferograms, removes all measurements that are affected by unstable pointing conditions, e.g., due to intermittent thin clouds disturbing solar-tracking (e.g., Klappenbach et al, 2015). The spectral bandwidth of the EM27/SUN allows for the detection of H 2 O, O 2 , CO 2 , CH 4 , CO, (CO in combination with an additional channel described 10 by Hase et al (2016)) and other gases if present in significant amounts (Butz et al, 2017). Related species for this study are O 2 and CH 4 .…”
mentioning
confidence: 99%